Hepatic Chylothorax: An Uncommon Pleural Effusion - Aelia Akbar MD, MPH; Tara Hendrickson MD; Avinash Vangara MD; Stanley Marlowe DO; Akbar Hussain MD; Subramanya Shyam Ganti MBBS, MD (SAGE Publishing, 2023)
An 83-year-old male with chronic obstructive pulmonary disease and liver cirrhosis presented with confusion and dyspnea. On chest X-ray, he had the right mid to lower lung zone white out. Ultrasound-guided thoracentesis drained 1.5 L of milky white pleural fluid which was transudative according to chemical analysis. Transudative chylothorax in liver cirrhosis without ascites is rare, but can happen. When the flow of ascitic chylous fluid into the pleural space equals the rate of ascites production, clinical absence of detectable ascites will occur. Hepatic chylothorax is important and should be kept in differentials when evaluating patients with liver cirrhosis.